2002
DOI: 10.1016/s0735-1097(02)01800-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of left atrial appendage flow for prediction of long-term sinus rhythm maintenance in patients with nonvalvular atrial fibrillation

Abstract: In TEE-guided management of nonvalvular AF, high LAA flow velocity identifies patients with greater likelihood to remain in SR for one year after successful CV. Low LAA velocity is of limited value in identifying patients who will relapse into AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 27 publications
7
71
1
Order By: Relevance
“…Although there is increasing evidence of the LAA importance as a trigger for atrial arrhythmias, the literature is scarce on the mechanisms and factors that may contribute to it. Previous studies have demonstrated the value of LAA flow velocity in the prediction of sinus rhythm maintenance after electrical cardioversion and, recently, Kanda et al described an association between low LAA flow velocity and AF recurrence after catheter ablation in patients with persistent AF [28][29][30]. The current research suggests that LAA volume may be a surrogate of increased LAA arrhythmogenicity, similar to what happens with the LA volume: an enlarged LA is associated with electrical remodelling, which provides an arrhythmogenic substrate for AF triggers [31].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is increasing evidence of the LAA importance as a trigger for atrial arrhythmias, the literature is scarce on the mechanisms and factors that may contribute to it. Previous studies have demonstrated the value of LAA flow velocity in the prediction of sinus rhythm maintenance after electrical cardioversion and, recently, Kanda et al described an association between low LAA flow velocity and AF recurrence after catheter ablation in patients with persistent AF [28][29][30]. The current research suggests that LAA volume may be a surrogate of increased LAA arrhythmogenicity, similar to what happens with the LA volume: an enlarged LA is associated with electrical remodelling, which provides an arrhythmogenic substrate for AF triggers [31].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] The relationship between the LAA-V and cardiac rhythm has been described in patients who underwent cardioversion of persistent AF. [16][17][18][19][20] If LA function was maintained at a certain level, patients were more easily kept in SR after PV-cryo. However, we sometimes encountered patients with AF in which an LA contraction could hardly be recognized.…”
Section: Relation Between the Laa-v And Long-term Resultsmentioning
confidence: 99%
“…However, our subjects included some with a long AF-D (>10 years; n=18, 18% of all patients), large LAD (=60 mm; n=28, 28% of all patients), or low LAA-V (=20 cm/s; n=38, 38% of all patients). Long-standing AF, 14,15 a large left atrium, 14,15 and low LAA-V [16][17][18][19][20] all are considered negative predictive factors for both recovery and maintenance of SR.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…24 Our finding that 54 (70%) of 77 patients remained in SR after discharge is a reasonable outcome despite the inclusion of patients with a long (>10 years) AF-D (n=11, 14% of all patients), large (≥65 mm) LAd (n=8, 10% of all patients), and low (≤20 cm/s) LAA-V (n=21, 27% of all patients). Long-standing AF, 26-28 a large LA [26][27][28][29][30] (especially, LAd ≥65 mm 29,30 ), and low LAA-V [31][32][33][34][35] have been shown to be negative predictive factors for both the restoration and maintenance of SR. Yuda et al reported that AF-D was significantly longer in patients with a giant LA than those without 29 and it is known that LAA-V is closely related to LA size. 35 Thus, AF-D, LAd, and LAA-V are related.…”
Section: Discussionmentioning
confidence: 99%